Privacy, Porn, and Gay Sex Parties: The Carceral Governance of Homosexuality in Indonesia - Hendri Yulius Wijaya (Laws, 2021)
This article examines how the recent Indonesian Pornography Law renders homosexuality and/or homosexual acts intelligible to the Indonesia state and society by institutionalising them as criminal offences. By drawing on insights from queer studies and exploring the cases of gay arrests in the country, I demonstrate that certain same-sex sexual acts are more susceptible to criminalisation, especially when those acts blur the distinction between public and private. The deployment of the Pornography Law against gay people, together with the anti-LGBT media environment in the country, has carried consequences for LGBT individuals, particularly gay people, by making them visible, legible, and thus subject to state surveillance and control.